2020
DOI: 10.3390/biom10060959
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene: A Master Regulator of Salinity Stress Tolerance in Plants

Abstract: Salinity stress is one of the major threats to agricultural productivity across the globe. Research in the past three decades, therefore, has focused on analyzing the effects of salinity stress on the plants. Evidence gathered over the years supports the role of ethylene as a key regulator of salinity stress tolerance in plants. This gaseous plant hormone regulates many vital cellular processes starting from seed germination to photosynthesis for maintaining the plants’ growth and yield under salinity stress. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
98
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(127 citation statements)
references
References 171 publications
3
98
0
5
Order By: Relevance
“…The exogenous application of substances or signaling molecules can regulate the plant’s metabolism for stress tolerance. Studies have shown that sulfur (S) and ethylene regulate salt tolerance in plants [ 11 , 12 ] by regulating various cellular processes. Sulfur is a major constituent of many enzymes of the photosynthetic carbon reduction cycle, and S supplementation increases photosynthesis via modulating the photosynthesis machinery and activating the synthesis of antioxidants [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The exogenous application of substances or signaling molecules can regulate the plant’s metabolism for stress tolerance. Studies have shown that sulfur (S) and ethylene regulate salt tolerance in plants [ 11 , 12 ] by regulating various cellular processes. Sulfur is a major constituent of many enzymes of the photosynthetic carbon reduction cycle, and S supplementation increases photosynthesis via modulating the photosynthesis machinery and activating the synthesis of antioxidants [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ethylene production and S-assimilation had close margins with some common regulatory elements or metabolites [ 25 ] and S regulates abiotic stress tolerance via ethylene [ 26 ]. Ethylene increases the assimilation of nitrates and sulfates to reduce salinity-induced oxidative stress [ 12 ]. The influence of combined ethephon and S application on ABA content and their coordination in stomatal regulation has been only partially reported in other species, such as tomato [ 27 , 28 ], while this information could provide a new insight for controlling photosynthesis under salt stress.…”
Section: Introductionmentioning
confidence: 99%
“…Ethylene is a key modulator of plant response to salt stress, but its specific role in different plant species and plant developmental stages is unclear 24 , 27 , 32 . In Arabidopsis and other plants, including maize and tomato, ethylene positively regulates salt stress tolerance 25 , 45 47 , however, in other plant species, such as rice and tobacco, ethylene plays a negative role in salinity stress response 24 , 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Among these stresses, salinity is one of the leading causes of crop yield reduction [ 4 , 5 ]. According to the Food and Agriculture Organization (FAO), salinity affects more than 30% of the irrigated land area worldwide, resulting in a monetary loss of 27.3 billion USD per year [ 6 , 7 , 8 ]. This is a ubiquitous issue and currently no continent is completely free from soil salinity [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…At the onset of the stress, salt solutes cause accumulation of high concentration of rhizospheric ions (mainly Na+ and Cl−), thus reducing water uptake through the roots [ 13 , 14 ]. This consequently leads to depletion in water potential and osmotic imbalance, while at the same time excessive amounts of salt enter the plant’s transpiration system [ 8 , 12 , 13 ]. Therefore, salt stress affects plant performance in two ways, either as an inhibitor of water uptake (osmotic effect) or as an accumulator of ions, with subsequent toxic effects [ 14 ].…”
Section: Introductionmentioning
confidence: 99%